2018
DOI: 10.1101/264697
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Steering ecological-evolutionary dynamics during artificial selection of microbial communities

Abstract: How might we artificially select multi-species microbial communities to improve their functions? In the accompanying article, we have modeled a commensal community where Helper releases Byproduct essential to Manufacturer, and Manufacturer diverts a fraction fP of its growth to make Product. Low-density “Newborn communities” grow and mutate over time T into “Adult communities”, and Adult communities with the highest function (total Product) are randomly partitioned into Newborn communities of the next cycle. H… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…The growth function G captures the outcome of the ecological dynamics (i.e., the fraction of red particles) after founding populations are allowed to grow for a finite time interval T . We note similarity between the G function and the recently proposed "community-function landscape" (Xie and Shou, 2018). The shape of G depends on the value of particle traits θ (growth rates r 0 and r 1 , and competition parameters a 00 = a intra 0 , a 10 = a inter 0 , a 01 = a inter 1 , a 11 = a intra 1 ), but also on the bottleneck size at dilution B and the collective generation duration T .…”
Section: From Particle Ecology To Collective Phenotypesupporting
confidence: 55%
See 2 more Smart Citations
“…The growth function G captures the outcome of the ecological dynamics (i.e., the fraction of red particles) after founding populations are allowed to grow for a finite time interval T . We note similarity between the G function and the recently proposed "community-function landscape" (Xie and Shou, 2018). The shape of G depends on the value of particle traits θ (growth rates r 0 and r 1 , and competition parameters a 00 = a intra 0 , a 10 = a inter 0 , a 01 = a inter 1 , a 11 = a intra 1 ), but also on the bottleneck size at dilution B and the collective generation duration T .…”
Section: From Particle Ecology To Collective Phenotypesupporting
confidence: 55%
“…Indeed, simulations of multi-species assemblages have shown that evolution of interaction rates not only improves diversity-dependent fitness, but also increases collective "heritability", defined as the capacity of randomly seeded offspring communities to reach the same dynamical state as their parents (Ikegami and Hashimoto, 2002;Penn, 2003). Further studies have stressed the role of the extracellular environment and of specific interaction networks, pointing out that microscopic constrains can affect the capacity of communities to participate in evolutionary dynamics at the higher level (Williams and Lenton, 2007;Xie and Shou, 2018;Xie et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microbial communities influence ecosystems by cycling matter (1) and affect human health by facilitating food digestion or causing infections (2)(3)(4)(5). Cohabiting microbes in communities interact and can perform functions that none of the member species can achieve efficiently on their own (6,7).…”
Section: Introductionmentioning
confidence: 99%